What Do Our Future EFL Teachers Think about Using Mobile Devices in Class? - Zain, Dodi Siraj Muamar; A. Bowles, Freddie (Universitas Muhammadiyah Semarang, 2024)
This study is primarily aimed to investigate the beliefs and attitudes of Indonesian EFL pre-service teachers toward the use of mobile devices such as smartphones or tablets for learning and instructional practice in Indonesia. Furthermore, this phenomenological study attempted to reveal the factors affecting these two constructs from 20 Indonesian EFL pre-service teachers through semi-structured interviews. As teaching tools, the majority of the participants expressed their reluctance to use mobile devices as instructional tools in in-person classes. However, they acknowledged that this technology could facilitate online learning and agreed that this technology would become more popular in the future. Analysis of the data also revealed factors affecting beliefs and attitudes of pre-service teachers toward the use of mobile devices as instructional tools comprising perceived ease of use and perceived usefulness and other influencing elements of self-efficacy: enactive mastery and physiological arousal. Finally, this study presents implications and recommendations that can be a reference to optimize the integrated mobile technology for class instruction.